Dark whispers - Coville, Bruce (Coville, Bruce. Unicorn Chronicles, 2008)
Seeking to unravel the secret of the long enmity between unicorns and delvers, Cara travels through a strange underground world to the court of the centaur king, while on Earth, Beloved and her hunters make final plans to jump to the fantasy land of Luster and drive the unicorns to extinction.